Tingkat kekerabatan bahasa Bidayuh di Sarawak (Jurnal Bahasa, 2004)
The main focus of this article is to compare the basic vocabulary of four Bidayuh languages, which are Biatah language, Bau-Jagoi language, Bukar-Sadong language, and Selako-Lara language, and to determine the degree of relations between these languages. Then, the basic vocabulary of the four languages will be compared to the Malay language to observe the genetic relationship between these Bidayuh languages to the Malay language. The current study utilized the comparison of the basic vocabulary or lexicostatistical method to find the similarities and differences between the basic vocabularies of the four languages. The comparison also set out to identify the cognate words, calculate the cognate percentage between those languages, and also determine the degree of genetic relationship between the languages, based on the degree of language relation schedule suggested by Gudschinsky ( 1964). The results of the comparative analysis of the basic vocabulary showed that the four Bidayuh languages are classified as languages in the Bidayuh language family, and not dialects from the same language. These languages exhibit similarities in form and meaning as they are derived from a common source, i.e. the Bidayuh proto-language. The genetic relationship between Biatah, Bau-Jagoi and Bukar-Sadong languages to the Malay language is found to be quite far. However the Selako-Lara language seems to have a very close genetic relationship to the Malay language. The results of the current research shed light on the linguistic status of the Bidayuh languages in Sarawak, and also showed the relation between the languages to the Malay language.